Strategi Aparatur Gampong dalam Implementasi Program Kota Tanpa Kumuh (Studi Kasus Gampong Seutui Kota Banda Aceh) - dasfita, lia; amrina, firda; pahlevi, reja; sarah, siti; rahmat, juni (Sanger Journal: Social, Administration and Government Review, 2025)
The Kota Tanpa Kumuh (KOTAKU) program is a government initiative designed to reduce slums in urban areas by empowering communities and strengthening local institutions. This research aims to analyze the strategies employed by village officials to implement the KOTAKU program in Gampong Setui, Baiturrahman District, Banda Aceh City. Using a qualitative method, this study collected data through interviews, observation, and documentation. The findings revealed that the program's implementation in Gampong Setui faced several significant challenges, including a lack of coordination among institutions, low community participation, and a limited budget. To address these obstacles, village officials adopted various strategies. These included enhancing coordination through regular meetings, mapping priority areas for intervention, and forming a dedicated Community Self-Help Agency (BKM) to manage the program. The BKM was specifically tasked with overseeing program implementation and fostering community economic empowerment. Despite these efforts, a major hurdle remains: the lack of community participation in maintaining the newly built infrastructure, which directly impacts the program's long-term sustainability. This research underscores the need for more intensive interventions, such as focused socialization, deeper community engagement, and continuous monitoring and evaluation. It confirms that a collaborative approach, tailored to the specific needs of the local community, is essential for the success of the KOTAKU program. The study concludes with recommendations to strengthen inter-agency coordination and explore technological innovations to improve future program management.